HEIMAT IN DER THEOLOGIE Amélé Adamavi-Aho Ekué, Frank Mathwig, Matthias Zeindler, Heimat(en)? Beiträge zu einer Theologie der Migration, Theologischer Verlag Zürich, Zürich 2017, 206 S. - Supranowicz, Radosław (Studia Europaea Gnesnensia, 2019)
Homeland in Theology; rev. of: Amélé Adamavi-Aho Ekué, Frank Mathwig, Matthias Zeindler, Heimat(en)? Beiträge zu einer Theologie der Migration [Homeland(s)? Contributions to a Theology of Migration]